1979
DOI: 10.1901/jaba.1979.12-679
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Effects of Demand Characteristics on the Analogue Assessment of Heterosocial Competence

Abstract: The present study assessed the effects of a contextual demand manipulation (pretreatment assessment versus experiment) and an instructional demand manipulation (high demand for competent behavior versus neutral demand) on the analogue assessment of heterosocial competence. Also assessed was the interaction between each demand manipulation and subject characteristics (high-frequency dating/low heterosocially anxious versus low-frequency dating/high heterosocially anxious college males). Students were assigned r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Because of the possible reactivity of obtrusive assessment techniques, Kazdin (1979) advocates the use of unobtrusive measures. Martinez-Diaz and Edelstein (1979) found that instructions to act in a competent fashion versus neutral instructions did not affect heterosocial behavior, but portraying the measurement situation as pretreatment assessment versus an experiment did affect at least a few of the dependent variables. This points to the care with which behavior therapists must construct their assessment methods.…”
Section: Identification Of Controlling Variablesmentioning
confidence: 89%
See 4 more Smart Citations
“…Because of the possible reactivity of obtrusive assessment techniques, Kazdin (1979) advocates the use of unobtrusive measures. Martinez-Diaz and Edelstein (1979) found that instructions to act in a competent fashion versus neutral instructions did not affect heterosocial behavior, but portraying the measurement situation as pretreatment assessment versus an experiment did affect at least a few of the dependent variables. This points to the care with which behavior therapists must construct their assessment methods.…”
Section: Identification Of Controlling Variablesmentioning
confidence: 89%
“…The assessment technique selected must suit the response system that is being measured and reveal its important dimensions. Hence, overt motor behavior is most frequently measured by direct observation by trained observers (e.g., Kent et al, 1979), by mediators, or by self-recorders (e.g., Williams, 1979) in either naturalistic (e.g., Greenwood, Greenwood et al, 1979) or analogue situations (e.g., Martinez-Diaz and Edelstein, 1979). Physiological-emotional responses are usually measured in analogue situations, due to instrumentation requirements.…”
Section: Identification Of Target Behaviormentioning
confidence: 99%
See 3 more Smart Citations